Modos de subjetivação contemporâneos: Considerações psicanalíticas sobre desejo, alteridade e pulsão - Rocha, Tiago Humberto Rodrigues (2007)
This research agrees to Freud s concept: to insert man in the social order around him and to analyze human relations, intra e inter subjetively established. It is a theoretical research using the psychoanalytical method, in which some notes are drawn from conflict points. This study starts from a brief historical context and it tries to trace the subjetive behavior that arises along human biographic story. This work attempts to do a deep analysis about alter relations that are established between human beings and the way they affect the desired moments. Our contemporary days have aticipated the action as a way to flee from sadness, part of human loneliness, creating many psychic configurations in relation to our present time. Actually, modern times demonstrate new configurations to showing pain, as well as, ways of facing it. In order to a better understanding of the processing attitudes among men and inside oneself, this work has the main objetive to think about a different meta psychological articulation to help us to understand the relation of contemporary arrangements created to deal with the feeling of abandonment and its results within the desired condition. Analyzing the relations among men and its limits, it is necessary to rethink about existing ideas such as pulsing and their vicissitudes, desire, id, ego, and super-ego, pleasure and other ones and to create different ideas from a free mind, open to new thinking. It does not mean to forget old theoretical ideas but to search new ways of subjetive thinking that coexist with the ones already known.